Effect of the location of the foot impact point on ball velocity in a soccer penalty kick - Ravenscroft, J. C.; Linthorne, N. P. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The aim of this study was to identify the impact point on the foot that maximizes ball velocity in a soccer instep penalty kick. One male player performed 23 maximum-effort penalty kicks using a wide range of impact points along the length of his foot. The kicks were recorded by a video camera at 100 Hz and a biomechanical analysis was conducted to obtain measures of impact point, ball projection velocity, and kinematics of the kicking leg. We found that ball velocity was insensitive to the location of the impact point (at least for positions between the ankle joint and the base of the toes). This result suggests that players should consider other factors (such as shot accuracy, shot reliability, and foot comfort) when selecting the impact point.